Electrocatalytic 5-(hydroxymethyl)furfural Oxidation using High Surface Area Nickel Boride - Barwe, Stefan; Weidner, Jonas; Moralesa, Dulce M.; Schuhmann, Wolfgang (Angewandte Chemie International Edition, 2018)
The electrochemical oxidation of the biorefinery product 5-(hydroxymethyl)furfural (HMF) to 2,5-furandicarboxylic acid (FDCA), an important platform chemical for the polymer industry, is receiving increasing interest. FDCA-based polymers such as polyethylene 2,5-furandicarboxylate (PEF) are sustainable candidates for replacing polyethylene terephthalate (PET). Herein, we report the highly efficient electrocatalytic oxidation of HMF to FDCA, using Ni foam modified with high-surface-area nickel boride (NixB) as the electrode. Constant potential electrolysis in combination with HPLC revealed a high faradaic efficiency of close to 100 % towards the production of FDCA with a yield of 98.5 %. Operando electrochemistry coupled to ATR-IR spectroscopy indicated that HMF is oxidized preferentially via 5-hydroxymethyl-2-furancarboxylic acid rather than via 2,5-diformylfuran, which is in agreement with HPLC results. This study not only reports a low-cost active electrocatalyst material for the electrochemical oxidation of HMF to FDCA, but additionally provides insight into the reaction pathway.